The Prevalence of Dental Caries and Fluorosis in TaPanese a 1 Communities with Up to 1.4 ppm of Naturally Occurring - Akihito Tsutsui, DDS, PhD; Mlnoru Yagi, DDS, PhD; Alice M. Horowitz, PhD (Blackwell Synergy, 2000)
The purpose of this study was to determine the relationship between the concentration of fluoride in drinking water and the prevalence of dental caries and fluorosis in seven Japanese communities with different concentrations of fluoride occurring naturally in the drinking water